Effect of fertilizer composition and different varieties on yield, methane and nitrous oxide emission from rice field in East Java Indonesia - Slameto,; Fahrudin, Danil Eka; Saputra, Muhamad Wahyu (Frontiers in Agronomy, 2024)
Rice, as a staple food in several Asian countries, contributes to approximately 10% of greenhouse gas (GHG) emissions during its cultivation. Furthermore, nitrogen fertilization increases the accumulation of GHG emissions. This study aims to investigate GHG emissions, including methane (CH4) and nitrous Oxide (N2O) resulting from the common fertilizer variations used by farmers in Indonesia for two rice varieties, Way Apo Buru and Inpari 32, and their relationship to rice yield. The research was conducted from August to November 2022 in an open field located in Jember, Indonesia. Two rice varieties, Inpari 32 and Way Apo Buru, were employed in this study. Fertilization variations included Urea (46%-N), ZA (21%-N 24%-S), SP-36 (36%-P & 5%-S), KCl (250:100:50:50 kg ha-1) (P1); NPK (16%-N:16%-P:16%-K), Urea (46%-N), ZA (21%-N & 24%-S) (225:175:100 kg ha-1) (P2); NPK (12%-N:12%-P:17%-K), Urea (46%-N), ZA (21%-N & 24%-S) (175:150:100 kg ha-1) (P3); and NPKS (P1) + chicken manure fertilizer 5 tonnes ha-1 (P4). In this research, Inpari 32 rice achieved greater yields while also exhibiting higher global warming potential. Applying NPKS fertilizer in combination with 5 tonnes ha-1 of manure fertilizer (referred to as P4) resulted in a substantial increase in rice yield compared to alternative fertilizer formulations. The various inorganic fertilizers had a relatively similar influence on growth, production yield, and greenhouse gas emissions (CH4 and N2O). However, the fertilizer NPKS and 5 tonnes manure fertilizer resulted in the lowest CH4 emissions and global warming potential values.